Head-to-Head Comparison of 68Ga-DOTA-TATE and 68Ga-DOTA-JR11 PET/CT in Patients With Tumor-Induced Osteomalacia: A Prospective Study - Hou, Guozhu; Zhang, Yuwei; Liu, Yu; Wang, Peipei; Xia, Weibo; Xing, Xiaoping; Huo, Li; Li, Fang; Jing, Hongli (Frontiers in Oncology, 2022)
Background: The purpose of this study is to compare the sensitivity of 68Ga-DOTA-JR11 and 68Ga-DOTA-TATE PET/CT for detecting the responsible tumor of tumor-induced osteomalacia (TIO) and investigate if 68Ga-DOTA-JR11 PET/CT can identify the culprit tumor of TIO in multiple suspicious lesions in 68Ga-DOTA-TATE PET/CT. Methods: A total of 19 patients with suspected TIO were prospectively recruited in this study. Each patient underwent whole-body PET/CT scan 40-60 min post-injection using 68Ga-DOTA-TATE and 68Ga-DOTA-JR11 on the same PET/CT, respectively in sequence, and on consecutive days. The diagnosis of TIO was confirmed by the combination of the postsurgical pathological results of the tumor and clinical information. Results: Among the 19 patients with TIO who were included in this study, culprit tumors from all patients were confirmed pathologically. 68Ga-DOTA-TATE PET/CT positively identified the causative tumor in 18/19 patients, whereas 68Ga-DOTA-JR11 PET/CT was positive in 11/19 patients (94.7% vs. 57.9%, respectively; P<0.05). 68Ga-DOTA-TATE PET/CT demonstrated more than one increased focal activity in 7 patients for a total of 16 lesions (3 lesions each in 2 patients and 2 lesions each in the rest 5 patients). However, Seven of these 16 lesions showed concordant results on 68Ga-DOTA-JR11 PET/CT by demonstrating increased activity (one lesion in each of the 7 patients). The surgical specimens of the lesions in these 7 patients confirmed the phosphaturic mesenchymal tumor. A total of 11 culprit tumors were positive in both 68Ga-DOTA-TATE and 68Ga-DOTA-JR11 PET/CT. The SUVmax of 11 culprit tumors was significantly higher on 68Ga-DOTA-TATE PET/CT compared with that on 68Ga-DOTA-JR11 PET/CT [17.8±12.5 vs 6.8±6.2; P<0.05]. Conclusions: 68Ga-DOTA-TATE PET/CT is more sensitive to 68Ga-DOTA-JR11 PET/CT in the detection of culprit tumor of TIO. However, 68Ga-DOTA-JR11 PET/CT might be helpful to identify the tumor in multiple suspicious lesions in 68Ga-DOTA-TATE PET/CT.